Shannon the ocean fairy - Meadows, Daisy (New York : Scholastic, 2009)
Shannon, the Ocean Fairy, Rachel, and Kirsty set off on an adventure to locate three enchanted pearls that were stolen by Jack Frost.
4.5
3-6
Keywords: Fairies -- Juvenile fiction; Pearls -- Juvenile fiction; Theft -- Juvenile fiction; Frost, Jack (Fictitious character) -- Juvenile fiction; Fairies -- Fiction; Gems -- Fiction; Stealing -- Fiction; Jack Frost -- Fiction; Fairies -- Fiction; Gems -- Fiction; Theft -- Fiction; Frost, Jack (Fictional character) -- Fiction; Fairies -- Fiction; Magic -- Fiction; Ocean -- Fiction; Pearls -- Fiction